Internet Of Things (IOT) Based Health Telemonitoring System - K.Sugumaran, Sutharson; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2024)
The purpose of this work is to develop an Internet of Things (IoT)-based health telemonitoring system. IoT is an excellent method to reduce human effort and provide simple access to physical objects. With this technology, people could utilise wireless connections everywhere they go. In modern days, people do not have enough time to keep track of their health status because of their busy lifestyle. Therefore, a health monitoring system that follows users automatically is proposed in this work. This system uses an Arduino Uno R3 microcontroller integrated with suitable sensors to monitor their health parameters. The health data being collected by the prototype are heart rate, body temperature, and blood saturation level, as well as the health condition of a patient, in real time. In addition, Blynk application is utilised to store collected data in cloud platform. Results from this prototype shows that the the data could be collected consistently. The health data could be monitored, recorded, and stored in a database. The prototype showcases an effective utilisation of IoT in healthcare application, especially for elderly people in the future.